Comprehensive Sexual Education, Territories, and the Right to Sport among Girls and Adolescents in Córdoba, Argentina - Bosio, María Virginia (2025)
This article presents the systematization of a teaching practice developed within the framework of the Specialization in Comprehensive Sexuality Education (CSE), based on a series of pedagogical interventions carried out with girls and adolescent soccer players at a women’s soccer school in the Sierras Chicas region of Córdoba province. The purpose is to analyze how CSE, understood as a public policy of human rights, can guide teaching in popular sports contexts and contribute to problematizing gender inequalities in access to play and participation. The methodological strategy is qualitative and relies on records of the practice itself, such as lesson plans, field notes, collective work, participant feedback, and instances of critical self-evaluation in postgraduate contexts. The discussion incorporates contributions from the human rights-based approach, the intersectional perspective, and studies on public policy and CSE in Argentina, to interpret the teaching interventions as situated political acts. The results show that the sustained integration of Comprehensive Sexuality Education (CSE) into football work enables new ways of naming the body, processing conflicts, and challenging notions about who has the right to play and under what conditions. It is concluded that teaching practice, when embedded in critical and committed postgraduate training, can become a bridge between the letter of policies and the everyday experiences of girls and adolescents in their communities.